SnTe@MnO2‐SP Nanosheet–Based Intelligent Nanoplatform for Second Near‐Infrared Light–Mediated Cancer Theranostics. (15th July 2019) - Zhang, Hanjie; Zeng, Weiwei; Pan, Chao; Feng, Liwen; Ou, Meitong; Zeng, Xiaowei; Liang, Xin; Wu, Meiying; Ji, Xiaoyuan; Mei, Lin
Abstract: Near infrared light, especially the second near‐infrared light (NIR II) biowindows with deep penetration and high sensitivity are widely used for optical diagnosis and phototherapy. Here, a novel kind of 2D SnTe@MnO2 ‐SP nanosheet (NS)‐based nanoplatform is developed for cancer theranostics with NIR II‐mediated precise optical imaging and effective photothermal ablation of mouse xenografted tumors. The 2D SnTe@MnO2 ‐SP NSs are fabricated via a facile method combining ball‐milling and liquid exfoliation for synthesis of SnTe NSs, and surface coating MnO2 shell and soybean phospholipid (SP). The ultrathin SnTe@MnO2 ‐SP NSs reveal notably high photothermal conversion efficiency (38.2% in NIR I and 43.9% in NIR II). The SnTe@MnO2 ‐SP NSs inherently feature tumor microenvironment (TME)‐responsive biodegradability, and the main metabolite TeO3 2− shows great antitumor effect, coupling synergetic chemotherapy for cancer. Moreover, the SnTe@MnO2 ‐SP NSs also exhibit great potential for fluorescence, photoacoustic (PA), and photothermal imaging agents in the NIR II biowindow with much higher resolution and sensitivity. This is the first report, as far as is known, with such an inorganic nanoagent setting fluorescence/PA/photothermal imaging and photothermal therapy in NIR II biowindow and TME‐responsive biodegradability rolled into one, which provide insight into the clinical potential for cancer theranostics. Abstract : A second near‐infrared light (NIR II) mediated cancer theranostics based on 2D SnTe@MnO2 ‐SP nanosheets (NSs) is developed by coupling ball‐milling, liquid exfoliating, and surface coating. The 2D SnTe@MnO2 ‐SP NS platform exhibits multiple promising features including efficient photothermal conversion, multimodal and deep penetrative optical‐imaging in NIR II biowindow, tumor microenvironment–responsive biodegradability, and synergetic antitumor of the metabolite TeO3 2− .